Development of a Prophetic Character Education Model for Elementary School Students through the Work - Sari, Yessy Yanita; Solihati, Nani; Fatayan, Arum (Jurnal Kependidikan, 2022)
This study aims to develop a writing design for an anthology of stories of the prophets and companions to support the implementation of a prophetic character education program in elementary schools. The method used was the ADDIE research and development model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study were students at two elementary schools in Jakarta. Research instruments were in the form of interviews, questionnaires, and documentation. The data analysis technique used was descriptive analysis. The results of this study indicated that through literacy, reading and writing anthology books about the stories of the prophets and companions could develop the prophetic character of elementary school students. The anthology book of the stories of the prophets and companions underwent several trials and revisions before it was declared eligibility. The percentage before the eligibility revision was 66%, then after revision it becomes 98% feasibility of an anthology book of stories of the prophets and companions. Based on student responses, it produced a percentage of 90%, so that the book can be categorized as very practical and very effective for implementation in elementary schools. In the anthology book on the stories of the prophet and companions, there are four prophetic characters that are expected to be implemented in the daily lives of elementary school students, including the characters fatahan (smart), amanah (trustworthy), shidiq (honest), and tabligh (communicative).